Transcendence: what on earth are we talking about? - Daniël P. Veldsman (Acta Theologica)
Within the scope of contemporary discourses on transcendence, this article presents and critically discusses the four models of transcendence that have been identified by the Dutch theologian Wessel Stoker. Two questions guide the discussion, namely whether our thinking of transcendence is any more than an unconscious way of being caught up in certain hard-to-shake spatializing and/or representational schemas, and how far we can interpret/translate the various phenomena of transcendence in terms of modal transformations of the quality of our responses to the world and to others, setting aside all onto-theological constructions referring to a beyond. To answer these questions, an argument is developed and motivated for relocating reflection on transcendence, and at the same time, pointers are formulated that should be considered in pursuing an interdisciplinary understanding of transcendence. After all, for all its authority and prestige, the word “transcendent” is a relative term: It depends on what is being transcended, and there is a long list of candidates – the subject, the self, the sensible world, beings, even beings themselves – and so there is nothing to stop us from wondering whether it is to be added to the list as still one more thing to be transcended (Caputo & Scanlon 2007: 2). The world we live in with our thoughts, passions, delights, and whatever stirs the mortal frame must surely take on a deeper meaning. Songs are more than longitudinal sound vibrations, sunsets more than transverse electromagnetic oscillations, inspirations more than the discharge of neurons, all touched with a mystery that deepens the more we contemplate and seek to understand (Harrison 1985: 273).